Effect of Electrodeposition Time on the Growth Rate of Carbon Nanotubes (CNTs) - Faishol, Faishol; Andoko, Andoko; Suryanto, Heru; Prasetya, Riduwan (TRANSMISI, 2024)
Carbon Nanotubes (CNTs) are nano-sized carbon that resembles tubes and has the potential to be used in various aspects of applications. Some of the CNT carbon capture methods include arc discharge, lasser ablation, CVD and electrodeposition. The advantage of the electrodeposition method is that the production cost is cheap and the preparation is easy. Electrodeposition is the precipitation of substances by using a direct electric current, with CO2 as the reactant. Factors that affect the growth rate of CNT are voltage, temperature, carbon source, electrode and time. The variation of the electorative time used was 60 minutes, 90 minutes, 120 minutes, 150 minutes, 180 minutes. The data collection process begins by shaping and measuring the weight of the electrode (Ni) with a diameter of 2 cm CNT deposition area. measuring the weight and melting Li2CO3 at a temperature of 750. then the CO2 flow rate setting, voltage setting 5V and time setting were then characterized by SEM-EDX and XRD. The results of the study showed that the optimal time obtained with a time of 120 minutes, the resulting CNT deposition rate was 1,618 g cm-2 h-1. Then based on the characterization of XRD and SEM, it shows that the longer the electrodeposition time, the less impurities are contained in the results obtained.